TEACHING READING COMPREHENSION ON NARRATIVE TEXT USING NUMBERED HEADS TOGETHER TECHNIQUE - Andri, .; Supardi, Iwan; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract : the purpose of this research is to investigate the effectiveness of teaching reading comprehension on narrative text using numbered heads together technique. Numbered heads together is a technique that can make the students become more active in teaching learning. The writer uses Pre-experimental research and the sample of this research is the eleventh grade students of SMAN 2 Sungai Kakap in which consist of 32 students. The technique of data collecting used is measurement technique and the tool of data collecting is multiple choice test. The data were calculated with the result of students` pre-test is 5.03, the post-test is 7.38. The students` different score between pre-test and post-test is 2.35. From the calculation of t-test that the observed t-test is 13.23 with the degree of freedom 31which is the significant of level of 0.05. The writer finds out that the result of t-test is bigger than t-table (13.23 > 2,204). It is found that the Effect Size (ES) analysis of the effectiveness of teaching reading comprehension on narrative text using numbered heads together technique is 2.17. It is categorized â€œhighâ€. As the result, teaching reading comprehension on narrative text using numbered heads together technique is highly effective in terms of increasing the students` mean score of narrative text reading comprehension. Keywords : Reading, Narrative Text, Numbered Heads Together Abstrak : Tujuan penelitian ini untuk mengetahui efektivitas dari mengajar memahami teks naratif menggunakan tehnik numbered heads together untuk SMAN 2 Sungai Kakap tahun ajaran 2015/2016. Tehnik numbered heads togetherÂ  adalah sebuah tehnik yang bisa membuat siswa menjadi lebih aktif dalam proses belajar mengajar. Penulis menggunakan penelitian Pre-experimental. Sampel penelitian ini adalah siswa kelas sebelas SMAN 2 Sungai Kakap yang terdiri dari 32 siswa. Tehnik pengumpulan data penelitian ini menggunakan tehnique pengukuran dan alat pengumpulan datanya menggunakan soal pilihan ganda. Penghitungan data dari penelitian ini berdasarkan hasil pre-test 5,03 dan nilai post-test 7,38. Jumlah perbedaan nilai pre-test dan post-test adalah 2,38. Dari penghitungan t-test yang diobservasi adalah 13,23 dengan degree of freedom 31 dengan level signifikan 0,05. Penulis mendapatkan hasil effect size dari mengajar memahami teks naratif menggunakan numbered heads together sebesar 2,17. Hasil ini dikategorikan sebagai â€œtinggiâ€. Hasilnya, mengajar memahami teks naratif menggunakan tehnik numbered heads together sangat efektif dalam meningkatkan nilai rata rata siswa dalam memahami teks naratif. Kata Kunci :KemampuanMembaca, TeksNaratif,